Resolution of Employee Performance: The Influence of Organizational Culture and Competency with Transformational Leadership Style as Mediation - Risnawati, Evi; Soelistya, Djoko; Desembrianita, Eva (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The research aims to analyze the influence of organizational culture and competence on employee performance through transformational leadership style as a mediating variable at PT Swabina Gatra. The type of research used in this research is quantitative research. The sampling technique used in this research was non-probability sampling with saturated samples. The population and sample in this research were 150 employees. The results of this study show that organizational culture has a positive and significant influence on employee performance, competence does not have a positive and significant influence on employee performance, organizational culture has a positive and significant influence on transformational leadership style, competence does not have a positive and significant influence on leadership style transformation, and transformational leadership style have a positive and significant influence on employee performance, while the indirect influence of organizational culture on performance through transformational leadership style shows full mediation because the indirect influence is greater than the direct influence of organizational culture, and for the indirect influence of competence on employee performance through a transformational leadership style shows partial mediation because the direct influence is greater. Therefore, it is necessary to pay attention to the transformational leadership style to influence organizational culture by maintaining consistency and carrying out company commitments well, while the opportunities to increase competency given to employees are sufficient and need to be maintained fairly.